Asociaciones verbales en esquizofrénicos tratados con olanzapina frente a los tratados con neurolépticos convencionales - Fernández Trespalacios, José Luis; Jiménez Sánchez, María Pilar; Rivero Expósito, María del Prado; Guerra Amador, Basilia (Acción Psicológica, 2012)
Resumen Se formula una propuesta de relación entre la acción psicológica a desarrollar por la Psicología Social y el conocimiento generado por la disciplina. Se subrayan tres puntos principales, a saber, la existencia de un camino de ida y vuelta entre conocimiento y acción, la importancia que juega el análisis del contexto y la conveniencia de que la acción psicológica esté planificada como intervención social y psicosocial. Se subraya también el papel estratégico de la evaluación de programas y necesidades. Abstract Previous reports have shown that schizophrenic subjects obtain higher scores in both communal and idiosyncratic response indexes than normal subjects in the Kent-Rosanoff Association Test. These results can be interpreted as a higher number of stereotyped behaviours and a worse integration in the group, which would lead us to determine an abnormal cognitive performance in some schizophrenic patients. On the other hand, atypical neuroleptics not only have less side effects but also generate a better cognitive performance that affects the verbal association indexes. The purpose of the present paper was to study the verbal association performance in schizophrenic patients treated with typical antipsychotics in order to compare the results with those obtained in schizophrenic patients treated with olanzapine. The results denote better verbal association performances in the latter group